Implementasi Kurikulum 2013 Bagi Guru SMA Negeri Aceh Tamiang - Nursamsu, Nursamsu; Baihaqi, Baihaqi (Magister Pendidikan Biologi, Universitas Negeri Medan, 2016)
In order to meet the educational goals, teachers have to prepare the tools of learning. Those tools have the roles as the instrument of teaching and learning activities Teaching and learning activities have to be supported by interesting stages activities, so students have more focus and have the active roles in learning. The objectives of learning can be achieved if teachers can adapt the learning activities into the changing policies, one of them are, the 2013 curricula. This research aims to see the implementation of 2013 curicula in the learning activities of biology teachers in government highschool of Aceh Tamiang. The method used in this research is the descriptive qualitative. The samples are 10 biology teachers. The location of research are in government highschool in Aceh Tamiang, including SMA Negeri 1 Manyak Payed, SMA Negeri 2 Percontohan, SMA Negeri 1 Kejuruan Muda, SMA Negeri 2 patra Nusa dan SMA Negeri 2 Kejuruan Muda. The instruments of the research are 1) Observation 2) Interview. Result of Â this research shows that schools are implementing the 2013 curricula.However, the research shows that the implementation of 2013 curricula is not fully completed. This shows that socialization and the training are not fully implemented, the ineffective of the training of 2013 Curricula. Teachers are not in maximum effort in implementing the 2013 curricula because the limited of the organizing system, the resources are not sufficient, and the assessment that seems so difficult. The result of analysis above shows the teachers preparedness in implementing of 2013 curricula is categorized as not sufficient.